An audit of clinical problems and activities during consultations - R.J.E. Erasmus (South African Family Practice)
Objective: To audit the clinical problems and consultation activities in an urban primary care facility. Design: A cross-sectional prospective descriptive study. Setting: The out-patient divisions of the Department of Family Medicine, Faculty of Medicine, at HF Verwoerd Hospital in Pretoria. Method: Data on patient profiles, presenting problems, special investigations, referrals and duration of the consultations were gathered by the participating doctors for a period of 19 weeks. Results: The mean age of the patients was 46,1 years. 9 559 consultations, during which 17 096 problems were attended to, were recorded. The mean duration per consultation was twelve minutes, blood tests were performed on 5,4% of the patients and l0% underwent radiological investigations. The referral rate to specialist departments was 75,2%. Conclusions: The results provide a base from which future planning and management of the service in the Department can be improved, trends determined and the quality for both patients and personnel improved.